Life tables for sunn pest, Eurygaster integriceps (Heteroptera: Scutelleridae) in northern Iran. - Iranipour, S.; Pakdel, A. Kahrrazi; Radjabi, G.; Michaud, J. P. (My University, 2011)
Life table studies of sunn pest were carried out in Varamin, Iran, from 1998–2001 in order to determine stage-specific ortalities and the impact of specific natural enemies on population dynamics. Populations were sampled 2–3 times weekly in agricultural fields during the growing season and monthly during the period of dormancy at resting sites in nearby mountains some 30km away from cereal fields. Adults spend a period of 9–10 months in diapause and suffered overcompensatory, density-dependent mortality during this period. Variation in adult overwintering survival was inferred to be largely a function of the physiological condition of bugs that is reduced in a density-dependent manner by intraspecific competition for food among newly molted adults prior to migration to resting sites. Adult mortality emerged as the primary factor in key factor analysis, contributing 73% of the total variance in mortality. Other important factors were egg parasitism by Trissolcus vassilievi Mayr and adult parasitism by several species of Tachinidae. Although T. vassilievi made only a minor contribution to overall variance in total mortality, it had a significant effect on the number of newly molted adults, the life stage that is most damaging to cereal crops. The equilibrium level of the pest population in wheat fields was inferred to be ca. 72.6 adults m[superscript -2], a number that substantially exceeds the economic threshold that ranges from 3–5 adults m[superscript -2].
Citation: Iranipour, S., A. Kharrazi Pakdel, G. Radjabi, and J.P. Michaud. 2011. “Life Tables for Sunn Pest, Eurygaster Integriceps (Heteroptera: Scutelleridae) in Northern Iran.” Bulletin of Entomological Research 101 (1): 33–44. https://doi.org/10.1017/S0007485310000155.
Iranipour, S., A. Kharrazi Pakdel, G. Radjabi, and J.P. Michaud. 2011. “Life Tables for Sunn Pest, Eurygaster Integriceps (Heteroptera: Scutelleridae) in Northern Iran.” Bulletin of Entomological Research 101 (1): 33–44. https://doi.org/10.1017/S0007485310000155.
Keywords: Life tables; Parasitism; Population dynamics; Tachinidae; Trissolcus spp; Wheat